Perancangan Sistem Pemanenan Energi Surya Terintegrasi Kaca Bangunan, Studi Kasus: Gedung Bandar Lampung - Koko Friansa; Rishal Asri; Monna Rozana; FX Nugroho Soelami (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
In this paper, design of solar energy harvesting system which integrated in building glass window was proposed. The location as the design reference is Bandar Lampung Building. Bandar Lampung Building uses 90% of the glass on the outside walls building with facing the sunrise and sunset. The design solar energy harvesting system was consisted of solar glass and electronic power system. Solar glass using several mini PV affixed on the glass with space in between, so partially of sunlight pass into the room. The solar energy harvesting system used for DC house network and not connected to the grid system. The solar energy harvesting is also equipped with power electronic system such as MPPT, lead acid battery, and DC-DC converter. The design of solar energy harvesting system is using calculative method based on secondary data several references for this case. Area of the solar glass reaches 16.32 m2 for 1 office room scale. The ratio between PV and room glass about 0.35. The power average of the solar glass on the glass building with facing to the sunrise is about 74.35 W, and then the average power of the solar glass with facing to the sunlight about 161.32W.